Influence of physical activity on cancer development, treatment and prophylaxis - Schab, Katarzyna Ewa; Tańska, Aleksandra Maria; Kotuła, Lidia; Bąk, Tomasz Krzysztof; Smutek, Maciej Jan (Journal of Education, Health and Sport, 2017)
Activation of the growth factors pathways is involved in cell growth and proliferation and is associated with carcinogenesis. Many studies have shown an increase in blood growth factors concentrations after training. On the other hand, numerous organisations recommend physical activity in cancer therapy and prophylaxis. This two phenomena may actually cause confusion. The aim of this paper was to present findings on the significance of physical activity in course of neoplastic disease and dispel doubts concerning its role in cancer treatment.